Neuronal differentiation of human dental pulp stem cells induced by co-treatment of ergothioneine - Amarin Thongsuk; Peeratchai Seemaung; Phetcharat Phanthong; Kajohnkiart Janebodin; Nisarat Ruangsawasdi; Thanasup Gonmanee; Chareerut Phruksaniyom; Tarinee Chodchavanchai; Tatcha Balit; Kenneth L. White; Charoensri Thonabulsombat; Anupong Thongklam Songsaad (PLoS ONE, 2025)
Objective Human dental pulp stem cells (hDPSCs) are promising adult stem cells that present multilineage differentiation ability. Interestingly, ergothioneine (ERGO) has the potential to uptake into the organic cation transporter N1 (OCTN1) to promote neuronal differentiation. Therefore, this study aims to demonstrate the effect of co-treatment of ergothioneine on the neuronal differentiation of hDPSCs. Methods The hDPSCs were established from the impacted third molars. Subsequently, the hDPSCs investigated the cell viability with ergothioneine at concentrations of 0–500 µM for 30 hours. The non-cytotoxic concentration of ergothioneine was synergistically induced with the neuronal induction medium. The characteristics of differentiated cells were verified as neuronal cells (d-hDPSCs) by identification of the Nissl substance. The optimal concentration of ergothioneine, which triggered the highest neuronal differentiation of hDPSCs, was further confirmed by neuronal phenotypes via immunofluorescent staining, gene expression, and the ability of neurotransmitter release by intracellular calcium oscillation. Results The isolated cells from human dental pulp tissue were characterized as mesenchymal stem cells (MSCs), verified as hDPSCs. The cellular toxicity of ergothioneine was not observed up to 500 µM for 30 hours. The d-hDPSCs presented a neuronal-like shape and positively expressed the Nissl substance. Interestingly, the highest number of neuronal-like cells was detected at 500 µM of ergothioneine. These neuronal-like cells exhibited the synaptic vesicle glycoprotein 2A (SV2A) expression and dynamic change of intracellular Ca2+, suggesting potential functional neuronal characteristics. Furthermore, co-treatment of ergothioneine at 500 µM triggered neurogenic maturation by decreasing Nestin and NES expression and increasing Beta-III tubulin, TUBB3, and microtubule-associated protein 2 (MAP2) expression, respectively. Conclusion Co-treatment of ergothioneine at 500 µM can enhance neuronal differentiation, which has the potential to promote neurogenic maturation. Therefore, these findings suggest the alternative of using hDPSCs and the potential of ergothioneine co-treatment as stem cell-based therapy for further transplantation to cure various neurological diseases.